Pelatihan Akupresur terhadap Dukungan Tenaga Kesehatan dan Kader Kesehatan dalam Pencegahan Stunting - Tiyara Safitri; Dewi Mey Lestanti Mukodri; Jeni Cesi Cintiani (Midwifery and Nursing Research, 2026)
Background: Stunting is a chronic nutritional problem that has a long-term impact on children's growth and development. Acupressure as a complementary approach is considered to have the potential to support infant growth and development stimulation. However, the support of health workers and health cadres for the application of acupressure is highly dependent on their level of knowledge and attitude. Acupressure training can be an innovative strategy to increase their capacity, while strengthening support for stunting prevention programs. The purpose of this study was to determine the effectiveness of acupressure training in increasing the support of health workers and health cadres in the prevention of stunting in toddlers. Methods: This study used a quasi-experimental design with a one-group pre-test post-test design. The sample consisted of 10 health workers and health cadres in the working area of the Kampung Bugis Community Health Center, which was taken using total sampling. Data were collected using knowledge, attitude, and support questionnaires for both pre-test and post-test and analyzed using univariate techniques to determine the frequency distribution and bivariate analysis using a paired t-test to determine the pre-post difference in the support of health workers and health cadres in stunting prevention. Results: Analysis of the difference in support scores before the intervention was 56.20 and after the acupressure training intervention was 74.80, so the statistical test results showed a p-value < 0.05, which means there was a significant difference between support before and after acupressure training. Conclusion: The results of this study imply that acupressure training can be used as a strategy to strengthen the capacity of health workers and cadres in supporting stunting prevention programs. The integration of acupressure into Posyandu activities and primary health care services can enrich the promotive and preventive approaches that have so far focused more on nutritional interventions.